A practical approach to continuous glucose monitoring (rtCGM) and FreeStyle Libre systems (isCGM) in children and young people with Type 1 diabetes. (February 2022) - Soni, A; Wright, N; Agwu, JC; Timmis, A; Drew, J; Kershaw, M; Moudiotis, C; Regan, F; Williams, EC; Wan, Jessica; Ng, SM
Abstract: Real-time continuous glucose monitoring (rtCGM) and FreeStyle Libre glucose monitoring systems (isCGM) are new evolving technologies used in the management of Type 1 diabetes. They offer potential to improve diabetes control and reduce hypoglycaemia. rtCGM can be linked to insulin pump providing hybrid closed loop therapy. Families of children and young people are keen to have the benefit from these technologies. These are relatively expensive so it is important that health care professionals, families of children and young people (CYP) with diabetes are adequately trained in the use of these devices. Health care professionals need to be able to make patient selection based on individual needs and preferences to achieve maximum benefit. Association of Children's Diabetes Clinicians (ACDC) developed a comprehensive guideline in 2017 to help identify which patients may be most likely to benefit and how these technologies may be practically implemented. Since then new technologies have been introduced and the use of GCM has expanded in routine clinical practice. This article, aims to provide a practical approach and help identify which patients may be most likely to benefit and how the technology may be implemented in order to maximise the clinical benefits.